Application of a microdosed cocktail of 3 oral factor Xa inhibitors to study drug-drug interactions with different perpetrator drugs - Mikus, Gerd; Foerster, Kathrin; Schaumäker, Marlene; Lehmann, Marie-Louise; Burhenne, Jürgen; Haefeli, Walter E. (British journal of clinical pharmacology, 2020)
Aims - Using 3 different perpetrators the impact of voriconazole, cobicistat and rifampicin (single dose), we evaluated the suitability of a microdose cocktail of factor Xa inhibitors (FXaI; rivaroxaban, apixaban and edoxaban; 100 μg in total) to study drug–drug interactions.
First published: 11 March 2020
Gesehen am 11.01.2022